2003
DOI: 10.1128/mcb.23.1.306-321.2003
|View full text |Cite
|
Sign up to set email alerts
|

Two Different Drosophila ADA2 Homologues Are Present in Distinct GCN5 Histone Acetyltransferase-Containing Complexes

Abstract: We have isolated a novel Drosophila (d) gene coding for two distinct proteins via alternative splicing: a homologue of the yeast adaptor protein ADA2, dADA2a, and a subunit of RNA polymerase II (Pol II), dRPB4. Moreover, we have identified another gene in the Drosophila genome encoding a second ADA2 homologue (dADA2b). The two dADA2 homologues, as well as many putative ADA2 homologues from different species, all contain, in addition to the ZZ and SANT domains, several evolutionarily conserved domains. The dada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
135
1
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(151 citation statements)
references
References 69 publications
(78 reference statements)
6
135
1
9
Order By: Relevance
“…Interestingly, the yAda2 protein has two paralogues in metazoans: ADA2a and ADA2b (28,29). Although ADA2b is part of the HAT module of the SAGA complex, ADA2a was shown to be a subunit of the HAT module of the ATAC complex together with GCN5, ADA3, and SGF29 (18,28,29).…”
mentioning
confidence: 99%
“…Interestingly, the yAda2 protein has two paralogues in metazoans: ADA2a and ADA2b (28,29). Although ADA2b is part of the HAT module of the SAGA complex, ADA2a was shown to be a subunit of the HAT module of the ATAC complex together with GCN5, ADA3, and SGF29 (18,28,29).…”
mentioning
confidence: 99%
“…No role for ADA2 independent of Gcn5 has been characterized in Saccharomyces cerevisiae, although multiple forms of ADA2 exist in Drosophila melanogaster [16,22], plants [23], mice, and humans [17]. In Drosophila, ADA2a and ADA2b are required for normal development but have distinct functions [24].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several groups have reported that the Drosophila genome contains 2 distinct genes encoding ADA2 homologs: ADA2a and ADA2b. Biochemical characterization of the 2 ADA2 proteins demonstrated that both interact with the HAT/ GCN5 complex and participate in transcriptional activation [16]. However, functional differences between the 2 human ADA2 proteins, hADA2a and hADA2b, have been recently reported [17].…”
mentioning
confidence: 99%
“…It has already been demonstrated that dTAF10 is part of the dSAGA complex, while dTAF10b is a component of the dTFIID complex. 16,17,20 We also checked available Drosophila protein-protein interaction databases and collected the interaction partners of dTAF10 and dTAF10b. The results were visualized by using Cytoscape software.…”
Section: Dtaf10 and Dtaf10b Affect The Dna Repair Efficiencymentioning
confidence: 99%
“…The two dTAF10 proteins show different expression patterns in neuronal tissues during embryonic development and are present in different multiprotein complexes -dSAGA and dTFIID, respectively. [16][17][18] Recently, it has been reported that dTAF10 and dTAF10b have synergistic roles in the regulation of Drosophila morphogenesis and they are required for the activation of Halloween genes involved in ecdysone biosynthesis. [18][19][20] Taken together, these observations support the idea that functionally different TAFcontaining complexes participate in gene regulation.…”
Section: Introductionmentioning
confidence: 99%